Seroprevalence of Rubella Antibodies Among Reproductive-Age Women in The Municipality of Alasabaa-Libya - Abdulfatah Ramadan Swesi, (African Journal of Advanced Pure and Applied Sciences, 2024)
Rubella is a contagious viral infection resulting from the rubella virus, that is transmitted through breathing droplets while an inflamed person coughs or sneezes. Rubella is of the greatest concern when a woman contracts the virus during pregnancy, especially in the first trimester. In such cases, the virus can be devastating for the development of fetus and cause complications known as congenital rubella syndrome. Which can result in a wide range of severe birth defects including cardiac abnormalities, growth retardation, hearing impairments, and cataracts. This study aimed to determine the prevalence rate of rubella in women of reproductive age in the municipality of Alasabaa-Libya. A cross-sectional study was performed on a random sample of female students from the High Institute of Science and Technology-Alasabaa, during the period from March to May 2022. Blood samples were accumulated individually from 90 females aged 18-23 years and rubella antibodies were quantitated by using Cobas e 411 autoanalyzer. Overall, 78 (86.7%) had IgG positive antibody to rubella, whereas 12 (13.3%) were negative for the rubella IgG antibody. While all the participants 90(100%) showed negative for rubella IgM antibody. In conclusion, the results confirmed the high occurrence of rubella IgG antibody amongst enrolled women showing that they had immunity against rubella virus. But there are approximately 13.3% of assayed females continue to be prone to rubella virus infection. SO a regular third dose could be recommended in the country wide vaccine program to prevent outbreaks among young females.